Peningkatan pemahaman masyarakat tentang nyeri muskuloskeletal kronik dari aspek neuropsikorehabilitatif - Nindela, Rini; Prananjaya, Bintang Arroyantri; Fatimah, Nyimas (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Musculoskeletal pain is an unpleasant sensory and emotional experience associated with real or potential damage to musculoskeletal tissue. Musculoskeletal pain such as low back pain, osteoarthritis or rheumatoid arthritis can develop into chronic pain when it lasts more than 3 months. Chronic pain and psychological well-being are very closely related; chronic pain adversely affects psychological well-being and decreases the quality of life, on the contrary, psychological well-being also affects the subjective feeling of pain felt by the patient. Therefore, the treatment of musculoskeletal pain should be carried out comprehensively, not only with medication but also with physical exercise, so as not to proceed into chronic pain. After participating in this activity, the community is expected to have a sufficient understanding of musculoskeletal pain, psychological aspects of pain, and exercise programs that can be done independently at home to treat pain.